2008
DOI: 10.1007/s12310-008-9002-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Interventions in Schools: Developers’ Views of Implementation Barriers and Facilitators

Abstract: This study examined the factors that are important to successful implementation and sustainability of evidence-based interventions in school settings. Developers of interventions that have been designated as ''evidence-based'' in multiple vetted lists and registries available to schools participated in a structured interview. The interview focused on potential facilitators and barriers to implementation and sustainability of their intervention. The interviews were transcribed and coded to identify similarities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
358
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(403 citation statements)
references
References 12 publications
26
358
1
5
Order By: Relevance
“…Nadeem and Ringle (2016) found that de-adoption of CBITS was associated with district-level leadership changes, financial and workforce instability, and shifting priorities at the school-and district-level. As they point out, these sustainment barriers are common to those observed with other school-based mental health programs (Forman, Olin, Hoagwood, Crowe, & Saka, 2009;Stirman et al, 2012). Comprehensive integration of trauma-informed approaches into the larger school context and culture may help overcome these system-level sustainment barriers.…”
Section: Responding To Trauma and Resisting Retraumatizationmentioning
confidence: 90%
“…Nadeem and Ringle (2016) found that de-adoption of CBITS was associated with district-level leadership changes, financial and workforce instability, and shifting priorities at the school-and district-level. As they point out, these sustainment barriers are common to those observed with other school-based mental health programs (Forman, Olin, Hoagwood, Crowe, & Saka, 2009;Stirman et al, 2012). Comprehensive integration of trauma-informed approaches into the larger school context and culture may help overcome these system-level sustainment barriers.…”
Section: Responding To Trauma and Resisting Retraumatizationmentioning
confidence: 90%
“…Many commentators in the field of school-based interventions have identified a greater need for evidence regarding early intervention and promotion programs to ensure the quality of programs being implemented (Lyon et al 2014). Qualitative data regarding an intervention offers researchers a means of gaining an in-depth understanding of what participants think about the logistics of the program as well as whether they actually like doing it (Forman et al 2009). The use of qualitative data to inform program modification and assess acceptability is indispensable for any program evaluation (Fabiano et al 2014).…”
Section: Program Evaluation and Acceptabilitymentioning
confidence: 99%
“…The months of April and May are typically noted as months when school students experience more pronounced emotional and behavioral problematic behaviors. 20 There were increased distractions in the school schedule during the time of the study, including administration of Pennsylvania State School Assessments, which occurred during at least part of each school day for a 2-week period in March 2013. A more desirable time in the school year to conduct research would have been during the fall prior to the distractions that come with the Christmas and New Year holidays.…”
Section: Global Advances In Health and Medicinementioning
confidence: 99%